Apprenticeship and Vocational Education and Training in Israel. - Kuczera Małgorzata, Małgorzata; Bastianić Tanja, Tanja; Field Simon, Simon (Paris : Organization for Economic Cooperation & Development, 2018)
One of a series of studies on vocational education and training, this review assesses the apprenticeship system and vocational education and training in Israel and provides policy recommendations. Israel has experienced strong economic growth over the last decade, and labour shortages are.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Apprentices; Apprenticeship programs; Electronic books